Introduction to Web Programming: Building Simple Web Applications with PHP and MYSQL - Chaerul Hidayat; Muhammad Wahyudi; Novi Miswanti; Ranggi Fatmawan; Emi Sita Eriana (International Journal of Integrated Science and Technology, 2024)
Web programming is a skill that is increasingly in demand. This article is an attempt to fill the gap in web programming learning literature, especially for beginners. By presenting comprehensive yet digestible material, this article contributes to the development of web programming learning curriculum. The methodology used is a step-by-step approach from basic concepts to practical application. The main contribution of this article is the provision of an effective self-study guide, complete with exercises and small projects